Failure of intravenous lipid emulsion in treatment of cardiotoxicity caused by mixed overdose including dihydropyridine calcium channel blockers - Jović-Stošić, Jasmina; Putić, Vesna; Živanović, Dragan; Mladenov, Milica; Brajković, Gordana; Djordjević, Snežana (Vojnosanitetski pregled, 2017)
Introduction. Calcium channel blockers and beta-blockers are among the most frequently ingested cardiovascular drugs in self-poisoning causing significant mortality. Intravenous lipid emulsion (ILE) is reported as a potentially novel antidote for treatment of acute poisoning caused by some of these drugs. Case report. We presented two cases of poisoning with these drugs. The case 1, a 24-year-old woman ingested amplodipine, metformin and gliclazide for self-poisoning. She presented with tachycardia and hypotension. Laboratory analyses revealed hyperglycaemia and metabolic acidosis. Despite the treatment which included fluid resuscitation, vasopressors, intravenous calcium, glucagon and ILE, circulatory shock occurred. The patient died 10 hours after admission due to cardiac arrest refractory to cardiopulmonary resuscitation. The case 2, a 41-year old man, was found in a coma with empty packages of nifedipine, metoprolol and diazepam tablets. On admission vital signs included Glasgow Coma Scale (GCS) of 3, weak palpable pulses, undetectable blood pressure, and irregular breathing with oxygen saturation of 60%. An electrocardiography showed AV block (Mobitz II) with ventricular rate of 44/min with progression to third degree of AV block. In attempt to increase heart rate and blood pressure the following agents were administered: atropine boluses, normal saline with dopamine, glucagon, calcium chloride and ILE. Temporary transvenous pacemaker was placed, electrical capture was recorded, but without improvement in haemodynamics. Three hours after admission cardiac arrest happened and cardiopulmonary resuscitation was unsuccessful. Conclusion. Intravenous lipid emulsion may be ineffective in acute poisonings with amlodipine, nifedipine or metoprolol.
Keywords: poisoning; suicide; calcium channel blokers; adrenergic beta-antagonists; heart arrest; fat emulsions; intravenous